Maternal HIV and Paediatric Lung Health. (January 2017) - Slogrove, A.L.; Frigati, L.; Gray, D.M.
Summary: With improved prevention of mother to child transmission of HIV, paediatric HIV disease is less common. However, the number of HIV exposed but uninfected infants is growing. Exposure to maternal HIV impacts infant respiratory health through an increase in known risk factors such as increased preterm birth and low birth weight, suboptimal breastfeeding, increased psychosocial stressors and increased exposure to infective pathogens. Exposure to the HIV virus and altered maternal immune environment result in immunologic changes in the infant that may contribute to respiratory disease risk. HIV exposed infants are at increased risk for severe pneumonia with poorer outcomes compared to unexposed infants. Maternal ART and optimal nutrition, including breastfeeding in high infective disease burden settings, reduce morbidity and mortality in HIV exposed infants and should be prioritized. The impact of exposure to maternal HIV on normal lung growth and risk for chronic respiratory disease is unknown and warrants further investigation.